(untitled) (Journal of actual problems of jurisprudence, 2016)
Development of state and legal system in Kazakhstan due to numerous factors, the most important of which is interethnic harmony in the fundamental questions of social life. A priority of national and state policy in the Republic of Kazakhstan is the decision of the main tasks of ethnic policy based on the values of civil society, democracy and sovereignty. One of the main functions of the state is the regulation of interethnic relations, with strong political and legal framework that complies with the Constitution of the Republic of Kazakhstan. The important role of the Assembly of Peoples of Kazakhstan as a public institution harmonization of public policy and activities of non-governmental organizations on the implementation of national policy in the country.